2014
DOI: 10.1364/ol.39.000375
|View full text |Cite
|
Sign up to set email alerts
|

Dark current suppression of MgZnO metal-semiconductor-metal solar-blind ultraviolet photodetector by asymmetric electrode structures

Abstract: The application of asymmetric Schottky barrier and electrode area in an MgZnO metal-semiconductor-metal (MSM) solar-blind ultraviolet photodetector has been investigated by a physical-based numerical model in which the electron mobility is obtained by an ensemble Monte Carlo simulation combined with first principle calculations using the density functional theory. Compared with the experimental data of symmetric and asymmetric MSM structures based on ZnO substrate, the validity of this model is verified. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The performance of Mg x Zn 1− x O‐based DUVPDs can be further improved by reasonable design of electrode structures or doping of Mg x Zn 1− x O . Wang et al observed that compared with the DUV devices that used conventional electrode, MSM photodetectors utilizing semicircular and triangular electrodes displayed a 20.5% and 100% increase in photocurrent, respectively .…”
Section: Mgxzn1−xomentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of Mg x Zn 1− x O‐based DUVPDs can be further improved by reasonable design of electrode structures or doping of Mg x Zn 1− x O . Wang et al observed that compared with the DUV devices that used conventional electrode, MSM photodetectors utilizing semicircular and triangular electrodes displayed a 20.5% and 100% increase in photocurrent, respectively .…”
Section: Mgxzn1−xomentioning
confidence: 99%
“…Wang et al observed that compared with the DUV devices that used conventional electrode, MSM photodetectors utilizing semicircular and triangular electrodes displayed a 20.5% and 100% increase in photocurrent, respectively . Furthermore, by using asymmetric Schottky barrier and electrode area, the dark current of MSM photodetectors can be reduced by 20 times and 1.3 times, respectively, without a noticeable loss in photocurrent . The n‐type conduction of Mg x Zn 1− x O films can be overwhelmingly improved by 2 orders of magnitude through employing triethylgallium as the dopant source during MOCVD growth process .…”
Section: Mgxzn1−xomentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ZnO-based material is one of the best candidate materials for preparing UV photodetectors. [29][30][31][32][33] After years of development, UV photodetectors based on ZnO and ZnMgO films have made great process, which has been discussed in the previous reviews. [13][14][15] Notably, to improve the performance of ZnO-based UV photodetectors, various methods have been selected, such as surface treatment, surface plasmonic effect, mixed-phase material, and so on.…”
Section: Zno-based Film Photodetectorsmentioning
confidence: 99%
“…24) In 2014, our group has also found that asymmetric rectangular Schottky barriers and electrode areas in MgZnO MSM PDs have a lower dark current than the symmetric ones without apparent photocurrent scarification. 25) However, MgZnO MSM PDs with asymmetric semicircular and asymmetric triangular Schottky contacts to improve both the dark current and photocurrent characteristics have never been reported.…”
Section: Introductionmentioning
confidence: 99%